RETRACTED: Evaluation of the definition of mechanisation impact on efficiency in capital repair in Russia and Spain - Fatullaev Rustam; Borovkova Anastasia; Murtazova Lana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001